SAKDIYAH MA’RUF’S STAND-UP COMEDY: HUMOR AND SOCIAL CRITIQUE IN THE DIGITAL AGE - Rahmadhian, Fitrizal; Tambunan, Shuri Mariasih Gietty (International Review of Humanities Studies, 2026)
Stand-up comedy can challenge dominant discourses and dismantle stereotypes. This research focuses on an Indonesian female stand-up comedian, Sakdiyah Ma’ruf. Using textual analysis, the study investigates recorded performances available on YouTube between 2014 and 2025. Sakdiyah addresses critical social issues, including religious fundamentalism, terrorism, sexism, and gender-based violence. The study explores how she constructs her comedic persona through narratives of personal identity and social critique, and how she employs humor to negotiate sensitive topics while remaining acceptable to diverse audiences. Findings reveal that her themes remain consistent across performances, while her humor strategies, including structured narratives, deliberate word choices, and subtle satire, allow her to transform critique into accessible and empowering comedy. Furthermore, her adaptation to various platforms, ranging from digital media to mainstream television, underscores the multidimensional nature of her comedy and her ability to challenge social norms.